INTEGRATING LOCAL CUISINE INTO TOURISM TO CREATE ECONOMIC AND SOCIAL BENEFITS IN THE DIGITAL 4.0 ERA: MENGINTEGRASIKAN KULINER LOKAL KE DALAM PARIWISATA DALAM MENCIPTAKAN MANFAAT EKONOMI DAN SOSIAL DI ERA DIGITAL 4.0 - Otje Herman Wibowo (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
This research aims to integrate local culinary into tourism in creating economic and social benefits in the digital 4.0 era. Data collection techniques are documentation from relevant journals and literature sources such as Google Scholar. Data analysis with critical literature. The results of the study show that the integration of local culinary into tourism in the digital 4.0 era creates economic and social benefits. Local cuisine attracts tourists with the uniqueness of traditional dishes. Digital infrastructure and marketing increase the visibility of local culinary delights. Positive impacts on tourism and local communities, such as new income and jobs. The interaction of tourists and local residents through culinary increases cultural understanding, local identity and tolerance. Huge potential for sustainable economic and social benefits